MANAGEMENT OF LOGISTICS RISKS AT DOMESTIC ENTERPRISES IN WAR CONDITIONS - KHARUN, Olena; HRYTSYNA, Lesia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article, based on the results of the research, clarifies the definition of «risk», reveals the features of the concepts of «logistics risk» and «logistics risk management». The classification of logistics risks is given depending on the type of flow, place of occurrence, impact on the logistics system, nature of occurrence and forecasting capabilities. The principles of logistics risk management of industrial enterprises are investigated: maximum profit, optimal probability of outcome, optimal ratio of profit and risk value, optimal fluctuation of the result, minimization of the spectrum of possible risks and the degree of their impact on the activities of the business entity, adequacy of reaction, acceptance. The functions of logistics risk management in the activities of enterprises are identified: innovative, regulatory, protective, analytical. Methods of preventing and reducing the level of logistics risks are disclosed: diversification, insurance, reserving (risk absorption), avoidance, risk dissipation, risk limitation. Methods of minimizing logistics risks in the activities of enterprises are characterized: risk avoidance, localization, compensation, risk transfer (or reduction), insurance, i.e. transfer and distribution of risks between counterparties of the logistics system. Five main stages of the logistics risk management process are presented: identification of external and internal risks of the logistics system; performance of qualitative and quantitative risk assessment; analysis of the impact of risk factors; forecasting, modeling and consequences of decisions; assessment of the acceptability of logistics risk and selection of a management method.